Level of a diversity of soil surface insect in Kedah Bungalow rainforest lodges, Blangjerago district, Gayo Lues regency - Kasmawati Kasmawati; Khairil Khairil; M Ali Sarong; Ismul Huda; Dewi Andayani (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Keywords: Diversity Of Ground Surface Insects The research on the level of soil surface diversity in Rainforest Lodges Kedah Bungalow District, Blangjerago Subdistrict, Gayo Lues District, was conducted in September to November 2019. This study aims to determine the level of soil surface insect diversity in the Rainforest Lodges Low Kedah District Blangjerango, Regency of Gayo Lues. The study was cond ucted with an exploratory method and a quantitative approach. Sampling was carried out at 3 observation stations that represent tilted land and flat land, and using traps, and the determination of the location was carried out using the transect method along 50 meters. Every 5 meters laid traps, with a amount trap usage of 30 traps. Analysis of diversity data using the diversity index (H’). The Diversity Index (H ') at station 1 is 1,224 (moderate) station 2 is 1,870 (low) and at station 3 is 2.275 (moderate). Overall, the level of diversity of soil surface insects in Rainfores Lodges Kedah Bungalow, Blangjerago District, Gayo Lues Regency is moderate.Kata kunci : Keanekaragaman Insekta Permukaan Tanah. Penelitian Tingkat Keanekaragaman Insekta Permukaan Tanah di Kawasan Rainforest Lodges Kedah Bungalow Kecamatan Blangjerago, Kabupaten Gayo Lues, dilaksanakan pada bulan September sampai dengan November 2019. Penelitian ini bertujuan untuk mengetahui tingkat keanekaragaman insekta permukaan tanah di Kawasan Rainforest Lodges Kedah Bungalow Kecamatan Blangjerango, Kabupaten Gayo Lues. Penelitian dilakukan dengan metode ekploratif dan pendekatan kuantitatif. Pengambilan sampel dilakukan pada 3 stasiun pengamatan yang mewakili kemirigan tanah dan tanah datar, dan mengunakan jebakan, dan penentuan lokasi dilakukan dengan metode transek sepanjang 50 meter. Tiap 5 meter diletakkan jebakan, dengan total pengunaan jebakan perangkap 30 buah. Analisis data tingkat keanekaragama mengunakan indeks keanekaragaman (H’). Indeks tingkat Keanekaragaman (H’) pada stasiun 1 adalah 1,224 (sedang) stasiun 2 adalah 1.870 (rendah) dan pada stasiun 3 adalah 2,275(sedang). Secara keseluruhan Tingkat Keanekaragaman Insekta Permukaan Tanah di Kawasan Rainfores Lodges Kedah Bungalow Kecamatan Blangjerago, Kabupaten Gayo Lues adalah sedang.